2023
DOI: 10.1021/acscatal.2c05591
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of “Oxygen-/Water-Fueled” PET-RAFT Protocol Matched to Covalent Organic Frameworks

Abstract: The reactive oxygen species (ROS)-mediated photoinduced electron transfer reversible addition-fragmentation chain transfer (PET-RAFT) process is an attractive tool to enhance the oxygen tolerance of radical polymerization systems. In this paper, we investigate the relationship between the covalent organic framework (COF) structure and polymerization performance based on the O 2/H 2 O system by modulating the COF at atomic and molecular levels. We combine density functional theory (DFT) calculations and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Thus, the HOMO and LUMO are distributed in distinct locations, leading to the effective exciton dissociation and charge separation over TpBSe-COF. 14,60 Meanwhile, the electrostatic potential distribution of the proposed fragment of TpBSe-COF reveals the high delocalization of p-electrons, also proted from the introduction of benzoselenadiazole (Fig. 7b).…”
Section: Mechanism Explorationmentioning
confidence: 99%
“…Thus, the HOMO and LUMO are distributed in distinct locations, leading to the effective exciton dissociation and charge separation over TpBSe-COF. 14,60 Meanwhile, the electrostatic potential distribution of the proposed fragment of TpBSe-COF reveals the high delocalization of p-electrons, also proted from the introduction of benzoselenadiazole (Fig. 7b).…”
Section: Mechanism Explorationmentioning
confidence: 99%
“…Except for TtBda-Ferrocene-20, the optimized COFs (20%) all exhibited a stronger DMPO-OOH • signal relative to TtBda, which represents the signal of O 2 •– in DMSO (Figure k). , It should be noted that energy band structure indicated that the oxidation potential of the sample was not sufficient to directly oxidize water to produce hydroxyl radical (OH • ) . The strength of the signal of DMPO-OH • is compatible with that of DMPO-OOH • due to the rapid disproportionation of O 2 •– with H 2 O and thus the generation of OH • (Figure l). ,, The above results demonstrate the polymerization reaction rate dependence on the production intensity of ROS, which greatly relies on the photovoltaic properties of COFs, and prove the practical potential of the defective design idea of the D–A conformation. With a view to further illustrating the reliability of the mechanism, control experiments and radical scavenging experiments were carried out to visualize the key species that undergo the catalytic polymerization in an open environment (Figure m).…”
mentioning
confidence: 87%
“…Crystalline covalent organic frameworks (COFs) with well-defined and preprogrammable architectures are prospective catalyst candidates suitable for photocatalysis, as the need for functionally oriented construction at the molecular level is fulfilled. Photoinduced controlled radical polymerization technology provides an innovative means for polymer synthesis science to meet the demand of high-end polymer products, which is highly regarded for its capability of precise control of polymer structure, low energy consumption, and spatial/temporal control. However, oxygen sensitivity restricts its wide range of applications along with the prospect of industrialization, and a substantial effort has been devoted to the construction of oxygen-resistant polymerization systems . Among them, the COF-based photocatalyst-mediated “water-/oxygen-fueled” photoinduced electron/energy transfer reversible addition–fragmentation chain transfer polymerization (PET-RAFT) polymerization protocol based on the aqueous phase system reconsiders the undesirable medium oxygen as the feedstock for the reaction, which is a potential technology to fundamentally solve the difficulty of oxygen-resistant polymerization, and provides a greener and more sustainable strategy for the synthesis of polymeric materials. , Simultaneously, the versatility of COFs, as well as the great designable potential, provides fascinating operating space for pursuing efficient and rapid preparation of precision polymers in oxygen-enriched aqueous-phase environments. , …”
mentioning
confidence: 99%
“…In recent decades, remarkable advancements have been made in reticular chemistry, and one typical example is construction of covalent organic frameworks (COFs) by meticulously assembling discrete functional building blocks. Benefiting from the high surface area, predesignable topology, and tunable pore size, COFs have found a variety of applications. Especially, 2D-conjugated COFs with extended π-delocalization are regarded as excellent photocatalysts for organic transformations. One critical element to achieve COFs with exceptional photocatalytic activity is highly contingent upon the judicious selection of covalent linkage as it serves as a crucial charge transfer channel. , Among various types of linkages that have been explored, imine linkage is the most utilized in constructing COFs due to its easily accessible building blocks and the mild thermodynamic conditions required for Schiff base condensation.…”
Section: Introductionmentioning
confidence: 99%
“…9−14 One critical element to achieve COFs with exceptional photocatalytic activity is highly contingent upon the judicious selection of covalent linkage as it serves as a crucial charge transfer channel. 15,16 Among various types of linkages that have been explored, 17−20 imine linkage is the most utilized in constructing COFs due to its easily accessible building blocks and the mild thermodynamic conditions required for Schiff base condensation.…”
Section: ■ Introductionmentioning
confidence: 99%